PERBEDAAN DAYA TAHAN JANTUNG PARU DAN KOMPOSISI TUBUH; PERSENTASE LEMAK TUBUH ANTARA LANJUT USIA ANGGOTA SENAM TAI CHI, WAI TAN KUNG DAN SEDENTER - Novi Vicahyani Utami; Leonardo Lubis; Agustina Agustina (PAIFORI, 2018)
The benefits of Tai Chi and Wai Tan Kung exercises on cardiopulmonary endurance and body composition have become a controversial issue. The survey analytical computational study was performed to investigate the differences in cardiopulmonary endurance and body composition among elderly members of Tai Chi, Wai Tan Kung, and elderly sedentary. The study involved 10 elderly members of Tai Chi, 10 elderly members of Wai Tan Kung, and 10 elderly sedentary. The Astrand-Rhyming’s step test was conducted to measure the cardiopulmonary endurance. While the measurement of body composition (body fat percentage) was done using a skinfold caliper. The data were analyzed with an unpaired t-test(p<0.05). The results of the study indicated that cardiopulmonary endurance (VO2 max) and body composition (body fat percentage) of Tai Chi elderly members were the best of both Wai Tan Kung elderly members and of elderly sedentary; while cardiopulmonary endurance and body composition of Wai Tan Kung elderly members were better than those of elderly sedentary.